English in mind : workbook 1 - Puchta, Herbert; Stranks, Jeff (Cambridge: Cambridge University Press, 2010)
This second edition updates a course which has proven to be a perfect fit for classes the world over.
Keywords: English language -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; English language